Vendors’ perceptions on the bushmeat trade dynamics across West and central Africa during the COVID-19 pandemic: Lessons learned on sanitary measures and awareness campaigns - (:unkn) unknown (My University, 2024)
In West and central Africa, the bushmeat trade is a major societal issue with contrasting implications on biodiversity, health and economy. With the advent of the COVID-19 pandemic, bushmeat trade markets were hit by national bans of various amplitude and poorly apprehended socio-economic consequences. We studied perceptions on the impact of the COVID-19 pandemic and related governmental measures on the bushmeat trade dynamics through questionnaires addressed to 377 vendors across three West and central African countries. We showed that bushmeat vendors constitute a professional category engaged in profitable, long-term careers. Vendors generally agreed that the pandemic had a negative impact on their activities and the number of clients. However, we observed large discrepancies among national trade dynamics. Côte d'Ivoire was hardly hit by the bushmeat ban and perceived governmental measures as rather negative, whereas Cameroon generally did not report a temporary stop of bushmeat activities and engaged in the stockpiling of pangolin meat (the most trafficked wild mammals in the world), and Benin suffered from a weakened supply chain. Because such differences are rooted in the geography and political agenda of each country, predicting the impact of mitigation measures on the global dynamics of bushmeat markets might be an unrealistic task if national specificities are not considered. West and central African vendors generally did not believe that pangolins were involved in the pandemic, for the reason that people have always been eating pangolins and have never been sick. Given that genomic mechanisms can quickly turn a harmless viral strain into an emerging infectious disease, we recommend that future awareness campaigns through television and social networks -the main media consulted by vendorsalso include education on microbial evolution and host shift.
Keywords: African Research